Effective strategies to enhance communicative skills in the colombian adolescent population (2017)
Through recent years, many Colombian researchers have been working towards a better insight, on how to properly teach the abilities of the English language that allow communicating and interacting. To continue with this important investigation, the purpose of this project is to compile diverse experiences from different teachers in actual classroom situations, with the aim of enhancing the English listening and communicative abilities.